Dual role of natural molecules in bridging cancer and Alzheimer’s disease: insights from in silico simulations - Nigar Kantarci-Carsibasi; Munteha Girgin (The European Chemistry and Biotechnology Journal, 2025)
Cancer and Alzheimer's disease (AD) present significant socioeconomic challenges and remain without definitive cures. Existing chemotherapeutic and anti-Alzheimer drugs approved by the FDA offer limited efficacy and carry notable side effects, underscoring the need for safer, more effective therapies. Our research group has recently focused on identifying natural molecules to treat AD by targeting acetylcholinesterase. Building on this, the current study expands our approach through virtual screening of DrugBank and Zinc databases to discover natural compounds that inhibit Estrogen Receptor Alpha (ERα) for breast cancer treatment. Molecular docking and drugability analyzes identified four promising compounds: Queuine, Thiamine, Galantamine, and Folic Acid. The docking scores for Galantamine, Thiamine, Queuine, and Folic Acid were -8.8, -8.3, -8.0, and -7.5 kcal/mol, respectively. These molecules demonstrate interactions with key residues in the ERα binding site such as Glu 353 and Phe 404 through hydrogen bonding and pi-pi stacking. Similar interactions are also maintained in the FDA-approved selective Estrogen Receptor Modulators, Raloxifene and Tamoxifen. ADMET analysis indicated that these natural molecules possess favorable drug-like properties and offer a safety advantage, as they are less likely to induce deep vein thrombosis or pulmonary embolism, which are the serious side effects commonly associated with Raloxifene and Tamoxifen. A thorough literature review further highlights these compounds' neuroprotective effects, suggesting they could serve as dual-purpose therapeutics to address both cancer and AD, paving the way for integrated treatment strategies.